2022
DOI: 10.1021/acs.inorgchem.2c01899
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy-Mediated Z-Scheme Charge Transfer in a 2D/1D B-Doped g-C3N4/rGO/TiO2 Heterojunction Visible Light-Driven Photocatalyst for Simultaneous/Efficient Oxygen Reduction Reaction and Alcohol Oxidation

Abstract: Hydrogen peroxide (H2O2) is a powerful oxidant that directly or indirectly oxidizes many organic and inorganic contaminants. The photocatalytic generation of H2O2 is achieved by using a semiconductor photocatalyst in the presence of alcohol as a proton source. Herein, we have synthesized oxygen vacancy (Ov)-mediated TiO2/B-doped g-C3N4/rGO (TBCN@rGO) ternary heterostructures by a simple hydrothermal technique. Several characterization techniques were employed to explore the existence of oxygen vacancies in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…Additionally, the XPS band positioned at 717.3 eV represents the satellite peak, while the peak at 724.5 eV is ascribed to the Fe 3+ satellite peak of Fe 2 O 3 . These outcomes clearly confirm that Fe is present in both Fe 2+ and Fe 3+ valence states in the Fe 2 O 3 sample, which may be due to conversion of a small portion of Fe 3+ to Fe 2+ species during the synthesis procedure. , Furthermore, the XPS of O 1s shown in Figure b can be deconvoluted into two peaks at 529.2 and 530.9 eV attributed to Fe–O–Fe and −OH bonding, respectively. , The core XPS spectra of N 1s show peaks at 398.6 eV assigned to the sp 2 -hybridized pyridinic-bridged nitrogen atom, which has been bonded to a carbon atom (CN–C), while the peak centered at 399.8 eV represents the tertiary N–(C) 3 group in aromatic rings and that seen at 406.1 eV corresponds to the π–π* satellite peak (Figure c). Moreover, the XPS spectrum of C 1s comprises two distinct peaks with binding energies of 284.9 and 288.5 eV ascribed to intended (C–C/CC) carbon species and sp 2 hybridization with N–CN coordination, respectively (Figure d). , In addition, the binding energy (BE) of B 1s is located at 191.8 eV, which can be attributed to B–N coordination and further suggests that the boron atom is surrounded by three nitrogen atoms as shown in the inset image in Figure e. From B–N coordination, it can be concluded that boron atoms have substituted carbon atoms in the aromatic ring (Figure e).…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…Additionally, the XPS band positioned at 717.3 eV represents the satellite peak, while the peak at 724.5 eV is ascribed to the Fe 3+ satellite peak of Fe 2 O 3 . These outcomes clearly confirm that Fe is present in both Fe 2+ and Fe 3+ valence states in the Fe 2 O 3 sample, which may be due to conversion of a small portion of Fe 3+ to Fe 2+ species during the synthesis procedure. , Furthermore, the XPS of O 1s shown in Figure b can be deconvoluted into two peaks at 529.2 and 530.9 eV attributed to Fe–O–Fe and −OH bonding, respectively. , The core XPS spectra of N 1s show peaks at 398.6 eV assigned to the sp 2 -hybridized pyridinic-bridged nitrogen atom, which has been bonded to a carbon atom (CN–C), while the peak centered at 399.8 eV represents the tertiary N–(C) 3 group in aromatic rings and that seen at 406.1 eV corresponds to the π–π* satellite peak (Figure c). Moreover, the XPS spectrum of C 1s comprises two distinct peaks with binding energies of 284.9 and 288.5 eV ascribed to intended (C–C/CC) carbon species and sp 2 hybridization with N–CN coordination, respectively (Figure d). , In addition, the binding energy (BE) of B 1s is located at 191.8 eV, which can be attributed to B–N coordination and further suggests that the boron atom is surrounded by three nitrogen atoms as shown in the inset image in Figure e. From B–N coordination, it can be concluded that boron atoms have substituted carbon atoms in the aromatic ring (Figure e).…”
Section: Resultssupporting
confidence: 52%
“…For the energy sector, H 2 O 2 is a promising and green alternative to H 2 fuel due to its high energy density (1.72 MJ/kg in 50 wt % H 2 O 2 ), water solubility, facile storage, safe conveyance, and having H 2 O as a byproduct. However, the traditional anthraquinone method addresses nearly 95% of the global H 2 O 2 demand, which operates under elevated temperatures, produces intensive toxic byproducts, and uses organic solvents. , Moreover, direct H 2 O 2 preparation using H 2 , O 2 , and Pd or Pd/Au alloy is also explored extensively but the use of expensive noble metals and explosion characteristics of involved gases require extreme attention. , Hence, development of a green and budget-friendly preparation technique is of utmost necessity. As a sustainable and clean alternative, semiconductor-based artificial photocatalytic H 2 O 2 production employing renewable feedstock via (i) a direct two-electron single-step reaction, (ii) indirect one-electron two-step reaction, or (iii) a combination of two •OH species has received immense interest from the global research community. Over the years, diverse catalytic systems have been experimented on toward improved H 2 O 2 production, including metal sulfide/oxide/phosphide, MOFs, carbonaceous species, and polymeric organic materials; however, low visible photon absorption ability, faster carrier recombination, limited charge-transfer efficiency, and poor O 2 adsorption-activation capacity reduce the overall quantum efficiency. , Out of the abundant semiconductor photocatalysts tested so far, two-dimensional (2D) metal-free graphitic carbon nitride (g-C 3 N 4 ) has attracted tremendous attention toward photocatalytic H 2 O 2 generation and pollutant degradation due to its superb intrinsic characteristics. , Moreover, the conduction and valence band position of g-C 3 N 4 encourages O 2 reduction and restricts oxidative decomposition of H 2 O 2 compared to oxide-based systems. For the first time ever, Shiraishi et al reported the photocatalytic generation of H 2 O 2 from a g-C 3 N 4 framework in a water/alcohol medium, but in the absence of a sacrificial agent, the activity is too low because of faster charge carrier recombination and low adsorption of O 2 on the catalyst surface .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations